Evaluation of depredation activities of vertebrate pest species in cassava cultivation at sasa-ajibode, Ibadan, Oyo state, Nigeria (2022)
Cassava is the fourth most important food crop in developing countries, after rice, maize, and wheat. African giant rats (Cricetomys gambianus), cane rats/grasscutter (Thryonomys swinderianus), and birds such as bush fowl (Francolinus bicalcaratus), among others, cause considerable damage to cassava crops. The present study was conducted on an existing cassava farm located at Shasha- Ajibode, Akinyele Local Government of Ibadan, Oyo state. Systematic sampling was used to collect quantitative and qualitative damages in the study area. Data were analyzed using Analysis of variance (ANOVA) and means were separated using Least Significant Difference (LSD) at the level of significance of P≤0.05. The results showed that there were evidences of root damage done in plot 1 (21.67%), plot 2 (14.00%), and plot 3 (20.00%) at 14 Weeks After Planting (WAP). Plot 2 had the highest total stem cut percentage (36.36%) while plot 1 and 2 had the same percentage of total stem cut (31.82%). It was revealed that the position of the plots had no significant effect on the damage level caused by the vertebrate pests on cassava roots and stems. It can be inferred that even though the damage level was not significant, attention should be given to managing those rodent populations and damages so that they do not escalate to causing unbearable economic loss.